2000
DOI: 10.1046/j.1440-1770.2000.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc, lead and cadmium speciation in Dnieper water‐bodies

Abstract: Data on the concentrations and movements of Zn, Pb and Cd in Dnieper reservoirs and the Dnieper‐Bug estuary are considered. There is a clear trend of increasing concentrations, often two‐ to fourfold, of these materials from the 1960s to the end of the 1980s. Large increases may be explained as the result of increased human impact on the water‐bodies and also because of reduced water discharge in the Dnieper River (discharge has been reduced by nearly 10 km3 in recent years). At present, the average concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…A number of these occur as natural constituents of the earth crust including arsenic, cadmium, chromium, lead, mercury, manganese and so on [7,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…A number of these occur as natural constituents of the earth crust including arsenic, cadmium, chromium, lead, mercury, manganese and so on [7,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…This is plausible since higher concentrations of DOC have been reported in leachates from CWD [19]. The availability of cations can in turn be related to the formation of complexes with the soil organic matter [53,71]. Therefore, it is possible that divalent cations are being retained more strongly in the soil influenced by the older logs, where the accumulation of humic substances is higher [53].…”
Section: Effects On Soil Chemical Propertiesmentioning
confidence: 99%
“…DOM largely controls dissolved metals (i.e., metals passing through 0.45 μm filters) speciation (Florence, 1982). Numerous studies indicate that a large proportion of the trace metals found dissolved in natural waters are in the organic fraction (i.e., in the form of metal-DOM complexes) (Linnik, 2000). A major fraction of DOM in natural water (∼60%-70% of total dissolved organic carbon) is composed of humic substances which consist mainly of humic acid and fulvic acid.…”
Section: Introductionmentioning
confidence: 99%